Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1988
DOI: 10.1017/s0003598x00074007
|View full text |Cite
|
Sign up to set email alerts
|

The worms of Roman horses and other finds of intestinal parasite eggs from unpromising deposits

Abstract: The preservation of organic remains and environmental indicators in those soft, damp and colourful deposits that visually indicate ancient excreta is familiar. This note reports a horse parasite, and draws attention to preservation of valuable material in deposits much less promising in nature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 3 publications
0
18
0
1
Order By: Relevance
“…Among the internal parasites of equines, only the nematode Oxyurus equi (Schrank) seems likely to be preserved, as other candidates are believed to produce less robust eggs. It has been found from Roman Carlisle (Jones, Hutchinson & Nicholson, 1988), at a site where other evidence for stabling was (with hindsight) very clear. It is unfortunate that horses and other large domesticated mammals do not in nature have nests for, as a result, no fleas are associated with them (the association of human flea with pigs seems likely to be secondary, perhaps the consequence of the artificial confinement of relatively hairless modern pigs in ''nests'' by humans).…”
Section: Parasites Of Stockmentioning
confidence: 98%
“…Among the internal parasites of equines, only the nematode Oxyurus equi (Schrank) seems likely to be preserved, as other candidates are believed to produce less robust eggs. It has been found from Roman Carlisle (Jones, Hutchinson & Nicholson, 1988), at a site where other evidence for stabling was (with hindsight) very clear. It is unfortunate that horses and other large domesticated mammals do not in nature have nests for, as a result, no fleas are associated with them (the association of human flea with pigs seems likely to be secondary, perhaps the consequence of the artificial confinement of relatively hairless modern pigs in ''nests'' by humans).…”
Section: Parasites Of Stockmentioning
confidence: 98%
“…Since the earliest paleoparasitological studies, Ascaris eggs have been found in archaeological samples, especially in Europe (Taylor 1955, Pike 1967, Greig 1981, Jones et al 1988, Bouchet 1991, 1993, 1995, Bouchet & Paicheler 1995, Bouchet et al 1996, 1998, Rousset et al 1996, Fernandes et al 2005, Le Bailly et al 2005. At archaeological sites of South America, Ascaris sp.…”
Section: Discussionmentioning
confidence: 99%
“…Although Jones et al (1988) determined that parasite eggs are very resistant to decomposition, they are none theless susceptible to decomposition in certain en vironments as described by Herrmann and Schultz (1987) and Reinhard et al (1986). To assess the extent of decomposition of parasite eggs, it is es sential to monitor the preservation condition of mi croscopic remains such as pollen grains, fungal spores, and plant cuticle fragments, as well as mac roscopic remains such as seeds.…”
Section: Methodsmentioning
confidence: 97%